A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

EveryOne, EveryWhere, EveryWhen: Just water futures for three Living Rivers - R. Quentin Grafton; Anne Poelina; William Brian (Badger) Bates; Matthew Currell; David Doyle; Kirsty Howey; Cecilia Lake; Caroline McFarlane; Anthony McLarty; Nhat-Mai Nguyen; Sam Phelan; Patricia Riley; et al. (Water Security, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Brachiopod giants from the Mississippian (Asbian) of western Ireland: Fossil bioarchives of seasonality and symbiosis and far-field harbingers of climate change - Lucia Angiolini; Karem Azmy; Enrico Cannaò; Gaia Crippa; Eamon Doyle; Giovanna Della Porta; John Murray; Michael O'Connell; Marco Viaretti; David A.T. Harper (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A Simple Parameterization for the Inland Coastal Aerodynamic Roughness Length within Onshore Flows - James Hlywiak; Jagmohan Singh; Jesus Ruiz-Plancarte; David D. Flagg; Ryan Yamaguchi; David G. Ortiz-Suslow; James D. Doyle; Qing Wang; Xiaodong Hong; Lian Shen (Boundary-Layer Meteorology, 2026)
Research and operational numerical weather prediction models rely on bulk-layer parameterization techniques - primarily, the Monin-Obukhov Similarity theory - to compute vertical turbulent fluxes of momentum within the atmospheric surface layer (ASL). In this way, the aerodynamic roughness length and consequently the turbulent drag over land is assumed to be an intrinsic property of the surface, ignoring characteristics of the overlying flow. Although recognized to be invalid near heterogeneous surfaces, to date, no suitable alternatives have been developed for ASL parameterization near coastal environments. In these regions, drastic spatial gradients in surface thermal and roughness properties drive cross-coastal flows, leading to phenomena that directly contradict bulk-flux assumptions. Here, we define a flow-dependent, local, inland coastal aerodynamic roughness length $$Z_{0c}$$ for onshore flow conditions. Analysis of observations collected from a cross-shore array of inland flux towers anchored at the Monterey Bay, CA coastline from June to October 2021 during the Coastal Land-Air-Sea Interaction (CLASI) campaign reveals significant departures in $$Z_{0c}$$ from the expected homogeneous values for increasing wind speeds and inland fetches within 8 kilometers of the coast. These findings inform development of a physical framework describing a non-dimensional $$Z_{0c}$$ as a function of the residence time of the inland flow, a reference height, and a representative homogeneous roughness length. We explore these relationships using large-eddy simulations of a coastal onshore flow scenario to achieve general understanding of the spatial variability in $$Z_{0c}$$ . Finally, we present a baseline empirical relationship for $$Z_{0c}$$ based on the CLASI dataset under near-neutral, onshore flow conditions.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The New South Wales nearshore wave tool – an interactive platform integrating high-resolution wave data for enhanced coastal science and management - Thomas B. Doyle; Andrew Bradford; Sean Garber; Raimundo Ibaceta; Bradley D. Morris; Michael A. Kinsela; Timothy C. Ingleton; Iman Jizan; David Taylor; David J. Hanslow; Kym Bilham (Environmental Modelling & Software, 2025)

Rapid assessments accurately identify threatened Australian flora under IUCN Red List Criteria after megafires - Tom Le Breton; Mark K.J. Ooi; Sylvia Hay; Joe Atkinson; Doug Bickerton; Stephanie Cerato; Richard J.P. Davies; Chantelle Doyle; Rachael Gallagher; Bettina Ignacio; David Keith; Mellissa McCallum; et al. (Biological Conservation, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An enigmatic large discoidal fossil from the Pennsylvanian of County Clare, Ireland - John Murray; Breandán A. MacGabhann; Eamon Doyle; M. Gabriela Mángano; Shane Tyrrell; David A.T. Harper (Palaeoworld, 2024)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Visualization of real-time displacement time history superimposed with dynamic experiments using wireless smart sensors and augmented reality - Marlon Aguero; Derek Doyle; David Mascarenas; Fernando Moreu (Earthquake Engineering and Engineering Vibration, 2023)

A Comparison of Vessel Patch Materials in Tetralogy of Fallot Patients Using Virtual Surgery Techniques - Alessia Di Nardo; Leslie Louvelle; David A. Romero; Matthew Doyle; Thomas L. Forbes; Cristina H. Amon (Annals of Biomedical Engineering, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

Geochemical controls on mobilization of metals from a 100-year-old waste rock pile and implications for selection of cover amendments - Sarah Doyle; Linda Figueroa; David Heinze (Journal of Environmental Management, 2023)

Evidence of a selective and bi‐directional relationship between arbuscular mycorrhizal fungal and bacterial communities co‐inhabiting plant roots - Olga A. Lastovetsky; Tancredi Caruso; Fiona P. Brennan; David P. Wall; Sean McMahon; Evelyn Doyle (Environmental Microbiology, 2022)
Arbuscular mycorrhizal fungi (AMF) provide plants with vital mineral nutrients and co‐exist inside the roots alongside a complex community of bacterial endophytes. These co‐existing AMF and bacterial root communities have been studied individually and are known to be influenced in structure by different environmental parameters. However, the extent to which they are affected by environmental parameters and by each other is completely unknown. The current study addressed this knowledge gap by characterising AMF and bacterial communities inside plant roots from a natural and an agricultural ecosystem. Using multivariate modelling, the relative contribution of environmental parameters in structuring the two communities was quantified at different spatial scales. Using this model, it was possible to then remove the contribution of environmental parameters and show that the co‐existing AMF and bacterial communities were significantly correlated with each other, explaining up to 36% of each other's variance. Notably, this was not due to the presence of know AMF endobacteria, as removal of endobacterial reads maintained the significance of correlation. These findings provide the first empirical evidence of a selective and bi‐directional relationship between AMF and bacteria co‐inhibiting plant roots and indicate that a significant fraction of this covariation is due to biological and ecological interactions between them.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Correction to: Control of Drug-Excipient Particle Attributes with Droplet Microfluidic-based Extractive Solidification Enables Improved Powder Rheology - Denise Z. L. Ng; Arif Z. Nelson; Gareth Ward; David Lai; Patrick S. Doyle; Saif A. Khan (Pharmaceutical Research, 2022)

Relationships between ecosystem properties and sea-level rise vulnerability of tidal wetlands of the U.S. Mid-Atlantic - Tracy Elsey-Quirk; Elizabeth B. Watson; Kirk Raper; Danielle Kreeger; Bhanu Paudel; LeeAnn Haaf; Martha Maxwell-Doyle; Angela Padeletti; Erin Reilly; David J. Velinsky (Environmental Monitoring and Assessment, 2022)

Sediment Accumulation, Elevation Change, and the Vulnerability of Tidal Marshes in the Delaware Estuary and Barnegat Bay to Accelerated Sea Level Rise - LeeAnn Haaf; Elizabeth Burke Watson; Tracy Elsey-Quirk; Kirk Raper; Angela Padeletti; Martha Maxwell-Doyle; Danielle Kreeger; David J. Velinsky (Estuaries and Coasts, 2022)

Control of Drug-Excipient Particle Attributes with Droplet Microfluidic-based Extractive Solidification Enables Improved Powder Rheology - Denise Z. L. Ng; Arif Z. Nelson; Gareth Ward; David Lai; Patrick S. Doyle; Saif A. Khan (Pharmaceutical Research, 2022)

Density-dependent winter survival of immatures in an irruptive raptor with pulsed breeding - Rebecca A. McCabe; Jean-François Therrien; Karen Wiebe; Gilles Gauthier; David Brinker; Scott Weidensaul; Donald Reid; Frank I. Doyle; Karl-Otto Jacobsen; Tomas Aarvak; Ingar Jostein Øien; Roar Solheim; et al. (Oecologia, 2022)

Evidence of a range expansion in sunfish from 47 years of coastal sightings - Olga Lyashevska; Deirdre Brophy; Steve Wing; David G. Johns; Damien Haberlin; Thomas K. Doyle (Marine Biology, 2022)
Almost nothing is known about the historical abundance of the ocean sunfish. Yet as an ecologically and functionally important taxa, understanding changes in abundance may be a useful indicator of how our seas are responding to anthropogenic changes including overfishing and climate change. Within this context, sightings from a coastal bird observatory (51.26 $$^°$$ ∘ N, 9.30 $$^°$$ ∘ W) over a 47 year period (from April to October 1971–2017) provided the first long-term index of sunfish abundance. Using a general linear mixed effect model with a hurdle to deal with imperfect detectability and to model trends, a higher probability of detecting sunfish was found in the 1990s and 2000s. Continuous Plankton Recorder (CPR) phytoplankton color indices and the annual mean position of the 13 $$^{° }$$ ∘ C sea surface isotherm were significantly correlated with the probability of detecting sunfish. An increase in siphonophore abundance (as measured by the CPR) was also documented. However, this increase occurred 10–15 years after the sunfish increase and was not significantly correlated with sunfish abundance. Our results suggest that the observed increase in sunfish sightings is evidence of a range expansion because it was significantly correlated with the mean position of the 13 $$^{° }$$ ∘ C isotherm which moved northwards by over 200 km. Furthermore, the observed increase in sunfish occured 10 years before sunfish sightings are documented in Icelandic and Norwegian waters, and was concurrent with well-known range expansions for other fish species during the 1990s. This study demonstrates how sustained citizen science projects can provide unique insights on the historical abundance of this enigmatic species.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Temperature and precipitation at migratory grounds influence demographic trends of an Arctic‐breeding bird - Susan Doyle; David Cabot; Alyn Walsh; Richard Inger; Stuart Bearhop; Barry J. McMahon (Global Change Biology, 2020)
Anthropogenic climate disruption, including temperature and precipitation regime shifts, has been linked to animal population declines since the mid‐20th century. However, some species, such as Arctic‐breeding geese, have thrived during this period. An increased understanding of how climate disruption might link to demographic rates in thriving species is an important perspective in quantifying the impact of anthropogenic climate disruption on the global state of nature. The Greenland barnacle goose ( Branta leucopsis ) population has increased tenfold in abundance since the mid‐20th century. A concurrent weather regime shift towards warmer, wetter conditions occurred throughout its range in Greenland (breeding), Ireland and Scotland (wintering) and Iceland (spring and autumn staging). The aim of this study was to determine the relationship between weather and demographic rates of Greenland barnacle geese to discern the role of climate shifts in the population trend. We quantified the relationship between temperature and precipitation and Greenland barnacle goose survival and productivity over a 50 year period from 1968 to 2018. We detected significant positive relationships between warmer, wetter conditions on the Icelandic spring staging grounds and survival. We also detected contrasting relationships between warmer, wetter conditions during autumn staging and survival and productivity, with warm, dry conditions being the most favourable for productivity. Survival increased in the latter part of the study period, supporting the possibility that spring weather regime shifts contributed to the increasing population trend. This may be related to improved forage resources, as warming air temperatures have been shown to improve survival rates in several other Arctic and northern terrestrial herbivorous species through indirect bottom‐up effects on forage availability.

Campylobacter culture fails to correctly detect Campylobacter in 30% of positive patient stool specimens compared to non-cultural methods - Janice E. Buss; Michelle Cresse; Susan Doyle; Blake W. Buchan; David W. Craft; Steve Young (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Behavioral phenotyping and dopamine dynamics in mice with conditional deletion of the glutamate transporter GLT-1 in neurons: resistance to the acute locomotor effects of amphetamine - Kathryn D. Fischer; Alex C. W. Houston; Rajeev I. Desai; Michelle R. Doyle; Jack Bergman; Maha Mian; Rebekah Mannix; David L. Sulzer; Se Joon Choi; Eugene V. Mosharov; Nathaniel W. Hodgson; Anita Bechtholt; et al. (Psychopharmacology, 2018)

Quantifying larvae of the coralivorous seastar Acanthaster cf. solaris on the Great Barrier Reef using qPCR - Jason R. Doyle; A. David McKinnon; Sven Uthicke (Marine Biology, 2017)

Comparative analysis of spatial genetic structure in an ant–plant symbiosis reveals a tension zone and highlights speciation processes in tropical Africa - Rumsaïs Blatrix; Jean Peccoud; Céline Born; Finn Piatscheck; Laure Benoit; Mathieu Sauve; Champlain Djiéto‐Lordon; Christiane Atteke; Jan J. Wieringa; David J. Harris; Doyle McKey (Journal of Biogeography, 2017)
Aim Pleistocene climatic oscillations induced range fluctuations in African rain forest organisms and may have shaped species diversification through allopatric speciation events. We compared the spatial genetic structure of two forest species that live in obligate symbiosis and thus must have experienced the same range fluctuations, as a means to discriminate incipient speciation from transient differentiation simply resulting from past divergence. Location Western central Africa. Methods We genotyped 765 individuals of the tree Barteria fistulosa and 605 colonies of its symbiotic ant Tetraponera aethiops at 12 and 13 microsatellite loci, respectively. We compared the spatial genetic structure of the two symbionts by using Bayesian clustering algorithms, isolation‐by‐distance analyses and clines of synthetic alleles. We used species niche modelling (climatic and soil variables) to investigate ecological variables associated with genetic discontinuities in tree populations. Results The trees and the ants showed congruent patterns of spatial genetic structure. However, the trees showed a very steep genetic discontinuity between groups north and south of latitude 1° N, which was much weaker in the ants. There was no evidence for effective gene flow between the two tree lineages in contact at the transition zone, despite the presence of a few hybrids. Niche modelling did not predict the occurrence of northern trees south of this genetic transition, and vice versa. Main conclusions The genetic discontinuity near latitude 1° N is inferred to be a tension zone resulting from reproductive incompatibilities between previously allopatric tree lineages. This tension zone may have stabilized at a climatic transition (between boreal and austral seasonal regimes), and matches patterns of genetic structure previously observed in other forest plant species. Our results illustrate independent speciation between two species that live in specific and obligate symbiosis and suggest that a tension zone may separate lineages of several central African forest plants near the thermal equator.

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Human behaviour during and immediately following earthquake shaking: developing a methodological approach for analysing video footage - Emily Lambie; Thomas M. Wilson; David M. Johnston; Steven Jensen; Erik Brogt; Emma E. H. Doyle; Michael K. Lindell; William S. Helton (Natural Hazards, 2016)

Strategies to improve low copy transgenic events in Agrobacterium-mediated transformation of maize - Elumalai Sivamani; Xianggan Li; Samson Nalapalli; Yoshimi Barron; Anna Prairie; David Bradley; Michele Doyle; Qiudeng Que (Transgenic Research, 2015)

Elevated rates of mild cognitive impairment in HIV disease - David P. Sheppard; Jennifer E. Iudicello; Mark W. Bondi; Katie L. Doyle; Erin E. Morgan; Paul J. Massman; Paul E. Gilbert; Steven Paul Woods (Journal of NeuroVirology, 2015)

(-)-Stepholidine is a potent pan-dopamine receptor antagonist of both G protein- and β-arrestin-mediated signaling - Julie A. Meade; R. Benjamin Free; Nicole R. Miller; Lani S. Chun; Trevor B. Doyle; Amy E. Moritz; Jennie L. Conroy; Val J. Watts; David R. Sibley (Psychopharmacology, 2015)

The Monitoring Network of the Vancouver 2010 Olympics - Paul Joe; Bill Scott; Chris Doyle; George Isaac; Ismail Gultepe; Douglas Forsyth; Stewart Cober; Edwin Campos; Ivan Heckman; Norman Donaldson; David Hudak; Roy Rasmussen; et al. (Pure and Applied Geophysics, 2014)

Real-world impact of neurocognitive deficits in acute and early HIV infection - Katie L. Doyle; Erin E. Morgan; Sheldon Morris; Davey M. Smith; Susan Little; Jennifer E. Iudicello; Kaitlin Blackstone; David J. Moore; Igor Grant; Scott L. Letendre; Steven Paul Woods (Journal of NeuroVirology, 2013)

Two-Way Coupled Atmosphere-Ocean Modeling of the PhilEx Intensive Observational Periods - Paul May; James Doyle; Julie Pullen; Laura David (Oceanography, 2011)

The biology and ecology of the ocean sunfish Mola mola: a review of current knowledge and future research perspectives - Edward C. Pope; Graeme C. Hays; Tierney M. Thys; Thomas K. Doyle; David W. Sims; Nuno Queiroz; Victoria J. Hobson; Lukas Kubicek; Jonathan D. R. Houghton (Reviews in Fish Biology and Fisheries, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Stranding events provide indirect insights into the seasonality and persistence of jellyfish medusae (Cnidaria: Scyphozoa) - Jonathan David Roy Houghton; Thomas K. Doyle; John Davenport; Martin K. S. Lilley; Rory P. Wilson; Graeme C. Hays (Hydrobiologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Natural hybridization between a clonally propagated crop, cassava ( Manihot esculenta Crantz) and a wild relative in French Guiana - ANNE DUPUTIÉ; PATRICE DAVID; CHANTAL DEBAIN; DOYLE MCKEY (Molecular Ecology, 2007)
Because domestication rarely leads to speciation, domesticated populations often hybridize with wild relatives when they occur in close proximity. Little work has focused on this question in clonally propagated crops. If selection on the capacity for sexual reproduction has been relaxed, these crops would not be expected to hybridize with their wild relatives as frequently as seed‐propagated crops. Cassava is one of the most important clonally propagated plants in tropical agriculture. Gene flow between cassava and wild relatives has often been postulated, but never demonstrated in nature. We studied a population of a wild Manihot sp. in French Guiana, which was recently in contact with domesticated cassava, and characterized phenotypes (10 morphological traits) and genotypes (six microsatellite loci) of individuals in a transect parallel to the direction of hypothesized gene flow. Wild and domesticated populations were strongly differentiated at microsatellite loci. We identified many hybrids forming a continuum between these two populations, and phenotypic variation was strongly correlated with the degree of hybridization as determined by molecular markers. Analysis of linkage disequilibrium and of the diversity of hybrid pedigrees showed that hybridization has gone on for at least three generations and that no strong barrier prevents admixture of the populations. Hybrids were more heterozygous than either wild or domesticated individuals, and phenotypic comparisons suggested heterosis in vegetative traits. Our results also suggest that this situation is not uncommon, at least in French Guiana, and demonstrate the need for integrated management of wild and domesticated populations even in clonally propagated crops.

Microevolution in agricultural environments: how a traditional Amerindian farming practice favours heterozygosity in cassava ( Manihot esculenta Crantz, Euphorbiaceae) - Benoît Pujol; Patrice David; Doyle McKey (Ecology Letters, 2005)
We demonstrate a novel case of selection for heterozygosity in nature, involving inadvertent human selection on a population of domesticated plants. Amerindian farmers propagate cassava ( Manihot esculenta ) clonally by cuttings. Seedlings also appear spontaneously in fields, and farmers allow them to grow, later using some for cuttings. These ‘volunteers’ contribute new genotypes. However, many are inbred, whereas multiplied clones are highly heterozygous. We demonstrate the selective retention of heterozygous volunteers. When farmers weeded fields, they killed small volunteers, but retained large ones. Plant size and heterozygosity were correlated, and both increased after weeding. The process we document allows maintenance of genotypically diverse and heterozygous clonal stocks. Demonstrating heterosis in nature usually requires large sample sizes, but novel features of our system allowed escape of this constraint. Traditional agroecosystems offer unusual opportunities for the microevolutionary studies required to give on‐farm conservation of genetic resources a solid scientific basis.

Polychlorinated biphenyls and organochlorine pesticides in milk and blood of Canadian women during lactation - Jos Mes; John A. Doyle; Barrett R. Adams; David J. Davies; Davida Turton (Archives of Environmental Contamination and Toxicology, 1984)